Optimization of the excavator-automotive complex operation at excavation of fluvioglacial deposits of overburden in the quarry of Sosnivske granite deposit - О.О.; I.D.; A.O. (Технічна інженерія, 2023)
The article presents the results of scientific researches of determining the optimal ratio between the dump truck body capacity and excavator bucket capacity during the operation of excavator-auto-mobile complex under the conditions of developing overburden in the quarry of Sosnivske granite deposit.